An examination of the South African corporate law through the lens of ubuntu (The Pretoria Student Law Review, 2025)
This article submits that ubuntu is indubitably a constitutional value which informs the constitutional era. Constitutional supremacy mandates that all values and principles of the Constitution must be observed to avoid invalidation. As a result of this constitutional obligation, this article intends to examine the inclusion of ubuntu as a constitutional principle in South African corporate law. To achieve this objective, the article employs doctrinal legal research methodology, also known as the black letter law, which encompasses scrutiny of various relevant legal sources. This research methodology is selected due to its ability to address the question of what the law is. In this case, the article intends to determine the position of ubuntu as a constitutional principle in the context of the South African corporate law. The conclusion reached is that the South African corporate law contains significant traces of the ontological elements of ubuntu. This is reinforced by the clear correlation between the values of ubuntu and corporate law principles. Accordingly, several South African corporate law concepts seem to correlate with the principles of ubuntu. A number of examples are expounded upon. Nonetheless, there is still no express inclusion of ubuntu in corporate law.